Integration numerique de lois de comportement elastoviscoplastique endommageable et applications - Bergheau, Jean-Michel; Mottet, Gerard; Debordes, Olivier (European Journal of Computational Mechanics, 1998)
Numerical simulation of creep rupture of a reactor pressure vessel in a severe hypothetical accident needs to perfectly take account of interactions between creep phenomena and damage. This paper presents a numerical method for solving constitutive equations of a material behaviour model coupling elastoviscoplasticity and creep damage through the effective stress concept. The numerical technique rests upon a semi-implicit time integration of the constitutive equations. The method is validated on both simple 1 D cases the results of which can be compared to other numerical or analytical solutions and in the case of an axisymmetric reference problem ( RUPTHER 4 test) under thermal and mechanical loading. The efficiency of different tangent stiffness matrices is analysed.